Biodiversity of Migrant Birds in the Limboto Lake Region, Gorontalo Province - Mustamin Ibrahim; Ilyas H. Husain; Tutin Pratiwi Langaru (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The bird population in Indonesia is rich in diversity, this is based on the number of bird populations and environmental conditions that are still maintained so as to allow the birds to live. This study aims to describe the types of migratory birds in Lake Limboto. The method used in this study is the count point method and with 4 observation points for 7 days on different days. The starting point of the observations is carried out alternately for each station so that there are variations in the observation time at each station. Overall, the classification of migratory birds in the Limboto Lake area is classified as moderate with an index carbon index value of 1.79. Migratory birds found in the Lake Limboto area are 9 species of migratory birds belonging to 7 families with a total of 706 individuals. The highest index value H'= 1.63 is at station 1, the diversity index value is moderate and the lowest hidden index H'= 0 is at station 4, the index value is relatively low.